A Thematic Review of the Efficacy of Firms' Responses to Economic Crises: A Ugandan Perspective - Isabirye, Joel (Technium Social Sciences Journal, 2021)
This paper is a thematic review of the efficacy of firms' responses to economic crises. The review seeks to answer the question of: how effective are firm’s responses to economic crises? Basing on the three forms of response firms adopt during economic crises, the paper identifies the advantages and disadvantages of each response. From studies accessed, it was found that retrenchment responses may improve efficiency of the firm, and help the firm to survive. On the contrary, retrenchment may weaken the competitiveness of the firm, and might increase costs of the process in the long run. Investment responses are forward looking offering the best prospects of post-recovery performance. In the short term, they are good for developing innovative solutions during crises. The main disadvantage with investment response is the cost of getting it done. Ambidextrous responses are the most viable option, because they tap into the advantages of retrenchment and investment and assist the firms to tackle the disadvantages of each response. The review also found that the efficacy of each response is dependent on a web of other factors related to the firm. Thus, the efficacy of each response may vary from firm to firm because of their unique circumstances.